(untitled) (Semiárida, 2025)
Shrub encroachment is the increase of undesirable shrubs at the expense of grass productivity. In this study, the effectiveness of chemical treatments and roller chopping on shrubs was evaluated. The experiment was made at a ranch in Santiago del Estero, in an area with sown C4 pastures, over 4.5 years. Seven treatments were applied (five chemicals, one mechanical: roller chopping and control, without intervention) under a randomized design with pseudoreplicates. In each experimental unit, the cover, height, volume, and regrowth capacity of individual shrubs were evaluated. The level of damage to the shrubs was analyzed using ANOVA. The persistence of the treatments was assessed by regression analysis using a) LnHeight, b) LnRegrowth, c) LnCover, and d) LnVolume as dependent variables and “years post-treatment” as the response variable by depicting the chronological factor. β coefficients were interpreted as the woody plants growth rate. The effect of treatments, “years post-treatment”, and species on variables a, b, c, and d was assessed using a Linear Mixed Model. The roller chopping, Aminopyralid + Picloram + Triclopyr (1), and Aminopyralid + Fluroxypyr (2) showed the significant statically lowest β values, indicating greater longevity (effectiveness). Vachellia caven was severely affected by treatment (1) (p<0.0001). Additionally, roller chopping increased the number of sprouts (p<0.05) in Strombocarpa reptans, Vachellia caven, Neltuma nigra, and Geoffroea decorticans. The variables a, b, c, and d remained at low levels until the third year, after which they increased, indicating the recovery of shrub cover and volume, and suggesting the need for frequent perturbations.